North America: designed to accompany Cornell's High School Geography. - Cornell, S. S. (Sarah S.) (D. Appleton & Co., 1855)
This map shows North and Central America and the surrounding areas. Regions are shaded in color. Major cities, bodies of water, and geographic features are marked (with relief shown by hachures). On the back, there is a second map showing a portion of British America (present-day Canada) with different territories shaded in color and labeled. This map also has major cities, bodies of water, and geographic features marked.